2017
DOI: 10.1080/21501203.2017.1365314
|View full text |Cite
|
Sign up to set email alerts
|

Potential molecular mechanisms for fruiting body formation of Cordyceps illustrated in the case ofCordyceps sinensis

Abstract: The fruiting body formation mechanisms of Cordyceps sinensis are still unclear. To explore the mechanisms, proteins potentially related to the fruiting body formation, proteins from fruiting bodies, and mycelia of Cordyceps species were assessed by using two-dimensional fluorescence difference gel electrophoresis, and the differential expression proteins were identified by matrix-assisted laser desorption/ionisation tandem time of flight mass spectrometry. The results showed that 198 differential expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Additionally, some HSPs are important in growth-related processes, including cell division and DNA synthesis. In Cordyceps sinensis , Hsp 70 and Hsp 90 are generally in high expression in the ascoma, so they may be related to their formation and development [ 10 , 80 , 81 ]. According to Prodromou [ 82 ], Hsp 90 implies several biological processes dependent on ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some HSPs are important in growth-related processes, including cell division and DNA synthesis. In Cordyceps sinensis , Hsp 70 and Hsp 90 are generally in high expression in the ascoma, so they may be related to their formation and development [ 10 , 80 , 81 ]. According to Prodromou [ 82 ], Hsp 90 implies several biological processes dependent on ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In cluster 2, with 6 DAPs, had a sudden increase in expression upon transition from ST to PR and then a sudden decrease in expression upon shifting from PR to MF phase, indicating that they may play a major role in the fruiting body initiation, such as histidine phosphotransferase (HPt, T5A92Z), one cytochrome P450 protein (T5A735) and Mannitol-1-phosphate 5-dehydrogenase (MPD, T5AIP9) ( Table 2). For examples, MPD, a main enzyme for mannitol biosynthesis, was found to be abundance in the fruiting body of O. sinensis, compared to that in mycelia (Feng et al, 2017). As a result, it may increase the content of mannitol in O. sinensis, which was found to be related to fruiting body initiation and development of A. bisporus (Kulkarni, 1990).…”
Section: Hierarchical Clustering Analysis Of Daps Involved In Ros Metmentioning
confidence: 99%
“…Cordyceps is a large genus of entomogenous fungi found all over the world (Feng et al 2017). There are more than 700 species of entomopathogenic fungi, of which approximately 300 species have been reported to produce a fruiting body, namely, the Cordyceps mushroom (Hong et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2019) studied the conditions, including solid-state fermentation, that cause infection and C. militaris fruiting body formation in silkworms. Feng et al (2017) described the artificial in vivo mass production of C. militaris in silkworm pupae as a living host insect. Park et al (2019) reported that, in general, fruiting bodies are formed on the larval integuments of vegetable wasps and plant worms with Cordyceps.…”
Section: Introductionmentioning
confidence: 99%